دور الكفارات في تعزيز التكافل الاجتماعي - مشروع 'أوران' الخيري لأداء وتسيير الكفارات نموذجا - - بابا وموسى محمد; حمدي محمد (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
In the theoretical section of the study, it was presented the concept of penances, their different categories and the most important issues related to these expiations, also it is clarified the most important criteria by how the indigent can be known, especially at the present time. Since it is the category of the society merited to expiations, then through this study, it is clarified the real objectives related to the legislation of atonement in Islam and its various roles in achieving the social solidarity in societies. In the practical section, the research dealt with a model of a charity association project aimed in organizing the carrying out atonements in society, and in which we introduce the project, its importance in people's life, its motives and structure, then its goals and horizons, to be an additional block to associations specialized in professional charitable work, the goal of creating such these associations is to facilitate to people to carry out their penances, and to meet the necessities of the indigents so that to secure their basic requirements of life like a food and clothes and to truly practice the social solidarity.